2007
DOI: 10.1089/apc.2007.9986
|View full text |Cite
|
Sign up to set email alerts
|

Outreach Program Contacts: Do They Increase the Likelihood of Engagement and Retention in HIV Primary Care for Hard-to-Reach Patients?

Abstract: Engagement in HIV primary care and the receipt of antiretroviral therapy when clinically indicated offers patients the opportunity to experience HIV disease as a chronic illness. Yet many people, particularly those with comorbid mental health or substance abuse conditions and those who face multiple barriers to care, cycle in and out of care and thus can not reap the life-prolonging benefits of antiretroviral therapy. Although there is evidence about the impact of different interventions on adherence to HIV me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 17 publications
4
51
0
Order By: Relevance
“…In addition, increased frequency of contact with clinicians, peers, and paraprofessionals in or outside the medical office results in fewer gaps in care during the first 12 months of follow-up [39]. These preliminary studies suggest that navigators and supportive services help the most vulnerable populations to stay in care [39]. More data are needed, however, to better understand how clinic characteristics influence patient retention.…”
Section: What Data Are There?mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, increased frequency of contact with clinicians, peers, and paraprofessionals in or outside the medical office results in fewer gaps in care during the first 12 months of follow-up [39]. These preliminary studies suggest that navigators and supportive services help the most vulnerable populations to stay in care [39]. More data are needed, however, to better understand how clinic characteristics influence patient retention.…”
Section: What Data Are There?mentioning
confidence: 88%
“…Other studies suggest that supportive services help specific populations, such as substance users, those with psychiatric illnesses [44], and atrisk youth, to stay in care [40]. In addition, increased frequency of contact with clinicians, peers, and paraprofessionals in or outside the medical office results in fewer gaps in care during the first 12 months of follow-up [39]. These preliminary studies suggest that navigators and supportive services help the most vulnerable populations to stay in care [39].…”
Section: What Data Are There?mentioning
confidence: 99%
“…The length of the time interval or whether the time interval exceeds a pre-determine threshold, typically ranging between 4 and 12 months, can be used as the measure. [13][14][15] From the example in Figure 1, we see that patients B and D had a gap of over 6 months between completed visits, whereas patients A and C did not have a gap in care.…”
Section: Measures Of Retention In Carementioning
confidence: 98%
“…Delayed linkage and poor retention in outpatient HIV care have been associated with delayed receipt of antiretroviral medications, higher rates of viral load failure, and increased morbidity and mortality. [5][6][7][8][9][10][11][12][13][14][15][16][17] Beyond the effects on individual health, engagement in HIV care has important consequences for the public health as it plays a pivotal role in HIV transmission and secondary HIV infections. Studies have demonstrated reduced risk transmission behavior among HIVinfected patients engaged in clinical care, 18,19 and viral load suppression, which is achieved more commonly among those with better retention, 6,9 also reduces risk of transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation